Relationship between Stretchability of Garment Lining and Ease of Body Movement (Journal of Fiber Bioengineering and Informatics, 2020)
In this study, the effect of the stretchability of garment linings on the ease of body movement was examined experimentally. For this purpose, three types of women's jackets with different linings were used: 1) a jacket with stretchable linings along the back and side panels, 2) a jacket with stretchable linings along the sides, and 3) a jacket with standard linings of a stretch-resistant material. During the experiment, subjects wearing these jackets were instructed to abduct both arms at 90° and then adduct them 90° along a horizontal plane. To clarify the ease of body movements during this motion, a sensory evaluation was performed. Additionally, the extension of the jacket samples during these movements was measured using displacement sensors, and the tension generated in these samples was estimated based on the tensile properties of the material. Further, the effect on clothing pressure, which is known to be closely related to ease of body movement, was also examined. The experimental results confirmed that subjects experienced greater ease of body movement when donning jackets with linings that stretched more easily, which helped minimize the tension generated in the material and the clothing pressure. In addition, compared with the sample employing stretchable linings along the sides, the sample with stretchable linings both along the back and the sides afforded greater ease of body movement and less tension and clothing pressure. As samples with stretchable materials require less force for deformation during motion, wearers stated that they experienced greater ease of movement. Based on these observations, it was concluded that employing stretchable material throughout the jacket lining is an effective approach for producing garments offering greater ease of body movement.